f(x+4)=8(x+4)-2

Simple and best practice solution for f(x+4)=8(x+4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x+4)=8(x+4)-2 equation:


Simplifying
f(x + 4) = 8(x + 4) + -2

Reorder the terms:
f(4 + x) = 8(x + 4) + -2
(4 * f + x * f) = 8(x + 4) + -2
(4f + fx) = 8(x + 4) + -2

Reorder the terms:
4f + fx = 8(4 + x) + -2
4f + fx = (4 * 8 + x * 8) + -2
4f + fx = (32 + 8x) + -2

Reorder the terms:
4f + fx = 32 + -2 + 8x

Combine like terms: 32 + -2 = 30
4f + fx = 30 + 8x

Solving
4f + fx = 30 + 8x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Reorder the terms:
-30 + 4f + fx + -8x = 30 + 8x + -30 + -8x

Reorder the terms:
-30 + 4f + fx + -8x = 30 + -30 + 8x + -8x

Combine like terms: 30 + -30 = 0
-30 + 4f + fx + -8x = 0 + 8x + -8x
-30 + 4f + fx + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
-30 + 4f + fx + -8x = 0

The solution to this equation could not be determined.

See similar equations:

| (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) | | 1.25x=3.75 | | 2xsquared+8=0 | | -10x^2+79x+8= | | 4x^2-28x+13=0 | | k*3(x-12)-3x=12 | | -7(m)=-42 | | P=a+b+4csolving | | p(5)=10-2q | | 6x=-2x-4.5 | | p-6=-9 |

Equations solver categories